Financial markets and green innovation - Philippe Aghion; Lena Boneva; Johannes Breckenfelder; Luc Laeven; Conny Olovsson; Alexander Popov; Elena Rancoita (European Central Bank (ECB), 2022)
Fulfilling the commitments embedded in the Paris Agreement requires a climate-technology revolution. Patented innovation of low-carbon technologies is lower in the EU than in selected peers, and very heterogeneous across member states. We motivate this fact with an endogenous model of directed technical change with government policy and financial markets. Variations in carbon taxes, R&D investment, and venture capital investment explain a large share of the variation in green patents per capita in the data. We discuss implications for policy, concluding that governments can play a catalytic role in stimulating green innovation while the role of central banks is limited.
Keywords: E5; G1; O4; Q5; 330; Climate change; financial markets; directed technical change; public policy; centralbanks